(untitled) (Scottish Historical and Archaeological Internet Reports, 2009)
A possible access route and a small section of drystone walling were identified along with two pottery sherds. Little can be said about the structural evidence. It is clear, however, that there was once a much larger site here which has suffered significant erosion due to the soft conglomerate rock of the stack.